2/3x=x-6

Simple and best practice solution for 2/3x=x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2/3x=x-6 equation:



2/3x=x-6
We move all terms to the left:
2/3x-(x-6)=0
Domain of the equation: 3x!=0
x!=0/3
x!=0
x∈R
We get rid of parentheses
2/3x-x+6=0
We multiply all the terms by the denominator
-x*3x+6*3x+2=0
Wy multiply elements
-3x^2+18x+2=0
a = -3; b = 18; c = +2;
Δ = b2-4ac
Δ = 182-4·(-3)·2
Δ = 348
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{348}=\sqrt{4*87}=\sqrt{4}*\sqrt{87}=2\sqrt{87}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(18)-2\sqrt{87}}{2*-3}=\frac{-18-2\sqrt{87}}{-6} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(18)+2\sqrt{87}}{2*-3}=\frac{-18+2\sqrt{87}}{-6} $

See similar equations:

| 2/3x+1-4/x-3=0 | | 2b+4=3b+15 | | (2x+10)+(4x-10)=145 | | 2x+10+4x-10=145 | | x²-4x–9=6x² | | 3x/8=17 | | p(p+6)=5 | | 3b+18=2b-4 | | 4.8=3.2/t | | 10−u=85 | | 3y-18=2y-12 | | 12(2x+3)/5=48(x−1)/15 | | 4. -2x+2=3x-3 | | 3b+21=2b+8 | | 4(x−1)3=2x+1 | | 5x+5-2x=2x-5 | | 3a+18=2a+10 | | 4(x−1)/3=2x+1 | | -7x+6=2x-21 | | 16(p+24)= | | 3a+21=2a-2 | | 3=34(b-8) | | (x+2)/4+99=110 | | (x+2)4+99=110 | | 4(3x-4)=687 | | 3x-6=8x+8 | | -12m+40+42m+36=-74 | | 2x²–4x–70=0 | | 4t^2+12t=17 | | -12m+40+42m+36=-76 | | 7-4f=-13 | | X+7-8x/3=17/6+5x/2 |

Equations solver categories